2020
DOI: 10.1002/wsb.1094
|View full text |Cite
|
Sign up to set email alerts
|

Movement Ecology of Spring Wild Turkey Hunters on Public Lands in South Carolina, USA

Abstract: Wild turkeys (Meleagris gallopavo spp., hereafter turkey) are the second most pursued big game species in the United States. Turkey hunting occurs primarily during spring, and on publicly owned lands managers often monitor hunter numbers and harvest as components of managing hunter opportunity and satisfaction. Contemporary research has shown that hunting activity on public lands can influence male turkey behavior; hence, research detailing hunter behaviors is needed to better support informed management. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Previous studies have demonstrated that prolonged periods with deep snow restrict turkey movements (Kane et al, 2007;Porter, 1977;Roberts et al, 1995) and may lead to significant overwinter losses (Roberts et al, 1995), but fields of standing corn or residual waste corn can mitigate impacts of deep snow and influence distribution of turkeys in northern latitudes (Haroldson, 1996; (Fredericksen et al, 2000) or hunting pressure. Recent studies have demonstrated that hunting activities and hunter behavior may influence male turkey movements (Gerrits et al, 2020), roosting behaviors (Wakefield et al, 2020a), and daily gobbling activity (Chamberlain et al, 2018;Wightman et al, 2019), but these conclusions have not been universal (Collier et al, 2017;Gross et al, 2015). Without a thorough understanding of the influence of hunting activities on individual turkey behaviors in our study system, we surmise that detection of a different individual during a subsequent survey would mask unavailability, whether via harvest or abandonment, of individuals from previous surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that prolonged periods with deep snow restrict turkey movements (Kane et al, 2007;Porter, 1977;Roberts et al, 1995) and may lead to significant overwinter losses (Roberts et al, 1995), but fields of standing corn or residual waste corn can mitigate impacts of deep snow and influence distribution of turkeys in northern latitudes (Haroldson, 1996; (Fredericksen et al, 2000) or hunting pressure. Recent studies have demonstrated that hunting activities and hunter behavior may influence male turkey movements (Gerrits et al, 2020), roosting behaviors (Wakefield et al, 2020a), and daily gobbling activity (Chamberlain et al, 2018;Wightman et al, 2019), but these conclusions have not been universal (Collier et al, 2017;Gross et al, 2015). Without a thorough understanding of the influence of hunting activities on individual turkey behaviors in our study system, we surmise that detection of a different individual during a subsequent survey would mask unavailability, whether via harvest or abandonment, of individuals from previous surveys.…”
Section: Discussionmentioning
confidence: 99%
“…To filter hunter GPS data, we first omitted locations not associated with legal hunting hours. We erased locations falling within 150 m of campgrounds, picnic areas, and other WMA facilities (Gerrits et al 2020) and locations falling within 61 m of WMA check stations, which was based on the proximity of open hunting areas to those check stations. We clipped locations to a 610‐m buffer around the WMAs.…”
Section: Methodsmentioning
confidence: 99%
“…Given our objective to quantify space use during active hunting (Gerrits et al 2020), we censored locations as follows. We excluded camp locations by mapping hunter locations in ArcGIS (Esri, Redlands, CA, USA) and visually inspecting them to identify the centroid of clusters of each hunter's locations during night-time hours (defined as any locations outside legal shooting hours ±1 hr).…”
Section: Hunter Telemetry Datamentioning
confidence: 99%
“…We determined that most stationary locations (i.e., consecutive locations in camp) were contained within a 200-m radius of the cluster centroid; thus, we excluded from analysis any telemetry locations within a 200-m radius of hunter camps. We further censored locations to exclude those obtained during the scouting period, outside legal shooting hours plus a 1-hour buffer before and after (Lamont et al 2020), within 300 m of the check station (Gerrits et al 2020), and after the day of harvest (successful hunters only; Plante et al 2017).…”
Section: Hunter Telemetry Datamentioning
confidence: 99%